Real-time wireless temperature measurement system of infant incubator - Irawan Sukma; Wuwus Ardiatna; Novitasari Novitasari; Vera Permatasari; Siddiq Wahyu Hidayat; Asep Rahmat Hidayat; Khusnul Khotimah; Ihsan Supono (International Journal of Electrical and Computer Engineering (IJECE), 2023)
The internet of things (IoT) has allowed for ubiquitous measurement. Infant incubator temperature is one of crucial parts that need to be measured, especially for the stability and uniformity temperature. Based on the interpretation of IEC 60601-2-19, we proposed measurement method using IoT with the message queue telemetry transport (MQTT). In the 10,000 packet, the result shows the quality of service (QoS) level 2 of the system has the highest delay, however it has the lowest packet loss data than the other QoS. For 1 hour, the uniformity result and stability can fulfill the standards. Uniformity of 32°C, the lowest difference is point C with 0.32 °C, and the highest difference is point B with 0.75 °C. Uniformity of 36 °C, the lowest difference is point B with 0.27 °C, and the highest difference is point C with 0.79 °C. The stability of 32 °C and 36 °C is 0.32 °C and 0.44 °C, respectively. Moreover, the Kruskal Wallis test shows the highest difference average from point M is point A and B. It occurred because of the point A and B located far from the heater part, so the point A and B colder than point C.